Kekasaran Permukaan Resin Komposit Nanofilled dan Nanohybrid Setelah Paparan Asap Rokok Kretek - Johanna Chandra; Laksmiari Setyowati; Setyabudi Setyabudi (Universitas Airlangga, 2018)
Background: Cigarette smoking is a public health problem that may influence physical properties of dental composites. Surface roughness is one of the physical properties of restorative materials that can influence their success. The use of nanofilled and nanohybrid composites in dentistry has substantially increased over the past few years. Purpose: The purpose of this study was to evaluate the surface roughness of nanofilled and nanohybrid composite resins exposed to kretek cigarette smoke. Methods: Twelve cylindrical specimens were prepared of each material and divided into two groups (n=6). For the control groups, the specimens were immersed in distilled water for 24 hours at 37oC and the water was renewed daily. For the experimental groups, the specimens were exposed daily to kretek cigarette smoke, then washed and stored in distilled water at 37oC. After 21 days, specimens were measured using a Surface Roughness Tester and the data was statistically analyzed. Result: Independent-T Test revealed that there were statistically significant differences in the surface roughness between control and experimental groups both nanofilled and nanohybrid, and between experimental groups nanofilled and nanohybrid. Conclusion: The exposure to kretek cigarette smoke can significantly increase the surface roughness of nanohybrid composites more than nanofilled composites.